Selenium Removal from Aqueous Solution Using a Low-Cost Functional Ceramic Membrane Derived from Waste Cast Iron - Yoon, Sungmoon; Cho, Kang Hee; Kim, Minsung; Park, Seong Jik; Lee, Chang Gu; Choi, Nag Choul (Water (Switzerland), 2023)
The high affinity of iron-based byproducts for anion removal can facilitate wastewater treatment using membranes functionalized with such byproducts. In this study, a low-cost functional ceramic membrane (LFCM) based on waste cast iron (WCI) was fabricated and applied to remove selenium from aqueous solutions. The effect of roasting (1250 °C) on the raw material properties was analyzed by X-ray diffraction and specific surface area measurements. Upon roasting, zero-valent iron (Fe0) present in WCI was oxidized to hematite (Fe2O3), while the specific surface area of WCI increased from 2.040 to 4.303 m2/g. Raw WCI exhibited the highest Se(IV) and Se(VI) removal capacity among the prepared materials, and Se(IV) could be removed faster and more efficiently than Se(VI). The selenium removal properties of the synthesized LFCM were similar to those of WCI. This membrane could simultaneously and efficiently remove Se(IV) and turbidity-causing substances through filtration. The results are expected to provide insights into the fabrication of ceramic membranes using industrial byproducts for the removal of ionic contaminants from wastewater.
Keywords: Anion removal; Cost functionals; Functional ceramics; Functionalized; High affinity; Iron-based; Low-costs; Membrane-based; Selenium removal; Waste cast irons; adsorption; ceramic membrane; selenium removal; waste cast iron; wastewater